Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Turnover Intention Karyawan RSU “ABC” Jakarta Selatan - Kherina Maulidah; Syarif Ali; Dewi Cahyani Pangestuti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to determine the effect of workload and job satisfaction on turnover intention of employees at ABC General Hospital, South Jakarta. Research Methodology: This research is quantitive research using inferential analysis method and data processing using IBM SPSS 24. Collecting data through distributing quetionnaires to 130 empolyees of the South Jakarta ABC General Hospital. Result: The workload partially has a positive effect on the turnover intention. Job satisfaction partially has a negative effect on turnover intention. Workload and job satisfaction simultaneously the turnover intention. Limitations: The study only conducted research on two independent variables that could affect turnover intention, namely workload and job satisfaction and was carried out during pandemic so that researchers had difficultly coming directly to the field in the data search process. Contributions: This research is expected to be a source of reference for similar research in the future and for hospitals to pay attention to the workload given and increase employee job satisfaction in order to reduce turnover intention.